Thermal cycling of thermoelectric generators: The effect of heating rate - O'Shaughnessy, Seamus (My University, 2019)
Thermoelectric generators, or TEGs, are solid state devices which can convert heat directly into electricity according to the Seebeck effect. When thermoelectric generators are subjected to thermal cycling they can undergo severe performance degradation. In this study, an experimental rig is constructed which is capable of thermally cycling the heat delivered to commercially available thermoelectric generators. An experimental investigation is undertaken to elucidate the effects of the cycling and heating rate on the power generation performance of the generators over time. Three generator modules of the same specifications were subjected to different heating rates. The figure of merit, the electrical power output, the effective Seebeck coefficient and the internal resistance of the generators are measured to assess the evolution of the modules’ performance over 600 heating and cooling cycles. It is determined that all thermoelectric generators display power generation performance reductions, and that faster thermal cycling rates lead to both faster performance degradation and an overall greater performance drop. It is observed that the reduction of the figure of merit and power generation performance is primarily due to the increase of the internal resistance of the thermoelectric generators.
PUBLISHED
Keywords: Thermoelectric generator; Electricity generation; Thermal cycling; Life cycle analysis; Variable heating rate; Thermal stress; Nanoscience & Materials; Smart & Sustainable Planet